2013
DOI: 10.1007/s13760-013-0232-4
|View full text |Cite|
|
Sign up to set email alerts
|

Stimulation of adult neural stem cells with a novel glycolipid biosurfactant

Abstract: Glycolipids are amphipatic molecules which are highly expressed on cell membranes in skin and brain where they mediate several key cellular processes. Neural stem cells are defined as undifferentiated, proliferative, multipotential cells with extensive self-renewal and are responsive to brain injury. Di-rhamnolipid: α-L-rhamnopyranosyl-(1-2)α-L-rhamnopyranosyl-3-hydroxydecanoyl-3-hydroxydecanoic acid, also referred to as di-rhamnolipid BAC-3, is a glycolipid isolated from bacteria Pseudomonas aeruginosa. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, biosurfactants are composed of lipid and proteins and are compatible with the skin cell membrane (Stipcevic et al . ). While the majority of biosurfactant‐related work is focussed on biosurfactants that are produced extracellularly by micro‐organisms much less work has been carried out on cell‐bound biosurfactants many of which are produced by, for example, probiotic Lactobacilli strains which have the added advantage of being nontoxic, biodegradable and environmentally friendly (Satpute et al .…”
Section: Health‐related Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, biosurfactants are composed of lipid and proteins and are compatible with the skin cell membrane (Stipcevic et al . ). While the majority of biosurfactant‐related work is focussed on biosurfactants that are produced extracellularly by micro‐organisms much less work has been carried out on cell‐bound biosurfactants many of which are produced by, for example, probiotic Lactobacilli strains which have the added advantage of being nontoxic, biodegradable and environmentally friendly (Satpute et al .…”
Section: Health‐related Applicationsmentioning
confidence: 97%
“…The antibacterial preservatives used in the majority of personal care products are synthetic and can cause skin irritation and allergic reactions by interaction with keratin or collagen and elastin and encourage the removal of lipids from the skin surface and affect the skin cells themselves (Bujak et al 2015). On the other hand, biosurfactants are composed of lipid and proteins and are compatible with the skin cell membrane (Stipcevic et al 2013). While the majority of biosurfactant-related work is focussed on biosurfactants that are produced extracellularly by micro-organisms much less work has been carried out on cell-bound biosurfactants many of which are produced by, for example, probiotic Lactobacilli strains which have the added advantage of being nontoxic, biodegradable and environmentally friendly (Satpute et al 2016b).…”
Section: Dermatological Applicationsmentioning
confidence: 99%
“…Synthetic surfactants can cause skin irritation and allergic reactions by interaction with proteins such as keratin (cytoskeletal proteins) or collagen and elastin (extracellular matrix proteins); also they promote the removal of lipids from the epidermal surface and affect the living cells in the skin [13]. Contrarily, biosurfactants are composed of lipid and proteins that are compatible with the skin cells membrane [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The spheroids of NSCs can be well cultured and better characterized by the addition of epidermal growth factor, fibroblast growth factor 2 and B27 to the culture system in vitro ( Gage and Temple, 2013 ; Zhang et al, 2021 ). After the NSCs isolated from the lateral ventricle of adult mice were cultured in a specific medium with growth factors, the number of neurospheres increased significantly ( Stipcevic et al, 2013 ). Intracerebroventricular injection of 300,120 ng/d di-rhamnolipid could increase the number of nerve balls in the anterior lateral ventricle of adult mice ( Stipcevic et al, 2013 ).…”
Section: The Source Of Nscsmentioning
confidence: 99%
“…After the NSCs isolated from the lateral ventricle of adult mice were cultured in a specific medium with growth factors, the number of neurospheres increased significantly ( Stipcevic et al, 2013 ). Intracerebroventricular injection of 300,120 ng/d di-rhamnolipid could increase the number of nerve balls in the anterior lateral ventricle of adult mice ( Stipcevic et al, 2013 ). These studies have revealed that NSCs can be obtained from endogenous, expanded or established into stable cell lines in vitro , and then transplanted to the injured site for regeneration treatment.…”
Section: The Source Of Nscsmentioning
confidence: 99%